Dynamics of Social Support and Self-Acceptance in the Elderly in Class III Ba'a Rote Ndao Correctional Institution - Mooy, Yoan Casandra; Mage, Mernon Yerlinda Carlista; Anakaka, Dian Lestari (Journal of Health and Behavioral Science, 2024)
. Criminal behaviour can be committed by individuals of any age, including the elderly. For elderly inmates, the transition to a new social status often results in difficulty accepting themselves. Social support plays a vital role in facilitating this self-acceptance. This study aims to explore the dynamics of social support and self-acceptance among elderly inmates at Rote Ndao Correctional Facility. A qualitative approach was employed, utilizing interviews as the primary data collection method. Interpretative Phenomenological Analysis (IPA) was used to analyze the data, with purposive sampling employed to select participants. The findings reveal that elderly inmates receive various forms of social support, including emotional, instrumental, informational, spiritual, and esteem support. The self-acceptance process involves phases of rejection, self-perception, relationship building, feelings of equality, responsibility, self-confidence, hope, and eventual self-acceptance. These findings highlight the critical role of social support in fostering self-acceptance among elderly prisoners.